Asymmetry of the pelvis in Polish young adults - Bibrowicz, Karol; Szurmik, Tomasz; Ogrodzka-Ciechanowicz, Katarzyna; Hudakova, Zuzana; Gąsienica-Walczak, Bartłomiej; Kurzeja, Piotr (Frontiers in Psychology, 2023)
Introduction Symmetry is one of the criteria of correct body posture in upright position. The spatial positioning of the pelvic girdle is crucial to it. Functional and structural asymmetries within the lumbo-pelvic-hip complex can have a significant influence on the structure and functions of many human body organs and systems. The aim of the study was to present the results of inclinometer measurements of selected landmarks of the pelvic girdle in young adults aged 19–29. Methods The analysis of occurrence of spatial pelvic asymmetry was based on the authors’ original, clinical classification and the significance of the body mass and height for the analyzed asymmetries. The inclinometer measurements of the selected landmarks of the pelvic girdle were performed in a sample consisting of 300 young individuals. Then, the occurrences of the spatial asymmetry of the pelvis were analyzed based on the authors’ own clinical classification using alignment symmetry of the iliac crests, the anterior superior iliac spines and the trochanters major as a criterion. All study subjects with asymmetry <1 degree were treated as those with a symmetrical pelvis. Results The significance of gender, body mass and height for the analyzed asymmetries was assessed. Symmetric positioning of the iliac crests was observed in only 32% of the respondents. The iliac crest depression on the left side was more frequently observed – in 41% of the respondents. This occurred more often in women (44%) than in men (38%). In the group of women, the rotated pelvis was the most often observed (39.4%) asymmetry, while for men, it was the oblique pelvis (40%). More detailed analysis by pelvic asymmetry subtypes showed their statistical differentiation between women and men (p < 0.0001). Analysis of moderate rotation of the pelvis for men, were reported slightly higher values but these differences were not statistically significant (p = 0.253). Women, in turn, showed slightly higher mean values but here too, the differences were not statistically significant (p = 0.245). Discussion Asymmetries in the pelvis area are common; they were observed in less than three-quarters of the examined population. Oblique pelvis was found in less than a quarter of women and in more than one-third men with the predominant structural asymmetries. Rotated pelvis was observed in more than one-third of women and men with dominating functional asymmetries. There were no linear correlations between the body mass and height, and the angle of asymmetries.